PENGGGUNAAN MODEL MIND MAP DALAM PENINGKATAN PEMBELAJARAN PKN SISWA KELAS IV SD NEGERI AMBALKLIWONAN TAHUN AJARAN 2014/2015 - Mukhlisin, Ahmad Fahmi (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Application of Mind Map Model in Improving Civic Learning for the Fourth Grade Students of SD Negeri Ambalkliwonan in the Academic Year of 2014/2015. The objectives of this research is to improve Civics learning through the application of Mind Map model. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were fourth grade students of SD Negeri Ambalkliwonan in the Academic Year of 2014/2015 totaling 37 students. It was proven by the increase of learning outcomes in the first cycle 62.2%, in the second cycle 78.4%, and in the third cycle 97.3%. The result of this research shows that the application of Mind Map model can improve Civics learning. Keywords: Mind Map, learning improvement, Civics Abstrak: Pengggunaan Model Mind Map Dalam Peningkatan Pembelajaran PKn Siswa Kelas IV SD Negeri Ambalkliwonan. Tujuan penelitian ini untuk meningkatkan pembelajaran PKn melalui penggunaan model mind map. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam tiga siklus. Subjek penelitian adalah siswa kelas IV SD Negeri Ambalkliwonan tahun ajaran 2014/2015 dengan jumlah 37 siswa. Pada pratindakan persentase ketuntasan siswa baru mencapai 5,4%, setelah dilaksanakan tindakan pada siklus I persentase ketuntasan siswa meningkat menjadi 62,2%, pada siklus II 78,4 dan siklus III meningkat menjadi 97,3%. Hasil penelitian menunjukkan bahwa penggunaan model mind map dapat meningkatkan pembelajaran PKn. Kata kunci: mind map, pembelajaran, PKn